Partispasi Petani Muda pada Penerapan Teknologi Mulsa Plastik Hitam Perak Budidaya Cabai Rawit (Capsicum frutescens L.) di Kabupaten Cilacap - Alfi Nur Fadilah; Kusmiyati Kusmiyati; Chifayah Astuti (Politeknik Pembangunan Pertanian Bogor, 2020)
The decrease in the number of young farmers with age < 44 years about 3%, while old farmers with the age of > 45 years increased about 3% from 2013 to 2018, so that it could be a portion of farmers in Indonesia will continue to decline. The solution to solve these problems include changing the perspective and mindset of young farmers by involving various agribusiness activities, especially the cultivation of cayenne pepper through the application of technology Silver Black Plastic Mulch (MPHP) that can increase production and farmers ' income in a sustainable manner This research aims to describe the participation rate of young farmers, identify factors that encourage the participation of young farmers and analyze the relationship between the driving factors with the participation of young farmers in the application of MPHP technology in chili cultivation in the Wanareja district of Cilacap Regency. The study was conducted in Tambaksari Village, Wanareja District, Cilacap Regency, from April to June 2020. The sample in this study was 37 respondents who were determined using the Isaac and Michael formula. The research variables consisted of the internal factors, external factors, and the participation of young farmers through the application of MPHP. Analysis of the data used in this research is descriptive analysis, Spearman Rank correlation analysis. The results showed as many as 56.7% of respondents; young farmers put high participation in cayenne pepper cultivation using MPHP. Factors that encourage the involvement of young farmers through the application of MPHP in cayenne pepper culture are the characteristics of young farmers, leadership in groups, the role of extension workers, and the role of families. In contrast, the factors related to the participation of young farmers through the application of MPHP in cayenne pepper culture are leadership in groups and the role of extension workers.